2022
DOI: 10.1016/j.envres.2021.112272
|View full text |Cite
|
Sign up to set email alerts
|

The influence of weather conditions on the COVID-19 epidemic

Abstract: Studying the influence of weather conditions on the COVID-19 epidemic is an emerging field. However, existing studies in this area tend to utilize time-series data, which have certain limitations and fail to consider individual, social, and economic factors. Therefore, this study aimed to fill this gap. In this paper, we explored the influence of weather conditions on the COVID-19 epidemic using COVID-19-related prefecture-daily panel data collected in mainland China between January 1, 2020, and February 19, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…Numerous studies have been conducted on the impact of weather variables on the COVID-19 pandemic since the pandemic began in 2019, and heterogeneous results have been reported. While a great number of regional studies from different countries have shown an association between weather conditions and the COVID-19 pandemic [7][8][9][10][11], a large study review claimed the opposite [6]. Given the dynamic relationship among the environment, viruses, and populations, our study divided Taiwan into six regions to closely examine these dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been conducted on the impact of weather variables on the COVID-19 pandemic since the pandemic began in 2019, and heterogeneous results have been reported. While a great number of regional studies from different countries have shown an association between weather conditions and the COVID-19 pandemic [7][8][9][10][11], a large study review claimed the opposite [6]. Given the dynamic relationship among the environment, viruses, and populations, our study divided Taiwan into six regions to closely examine these dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…A large study review declared that there was no association between weather conditions and the COVID-19 pandemic [6], but several regional studies have shown a correlation [7][8][9][10]. Research focused on China highlights a positive correlation between temperature and the COVID-19 epidemic [7,11], while other studies suggest that rising temperatures may mitigate the expansion of the pandemic to some extent [12,13]. Ng et al (2024) provide similar insights for Malaysia, suggesting that regional climatic conditions significantly influence transmission dynamics across the country [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The existing literature mainly utilizes a generalized additive model 21 , generalized linear model, Spearman's correlation analysis 50 , 51 and Pearson's correlation analysis 52 . Regarding sample selection, the use of national-level samples alone fails to account for the regional variations in weather conditions among countries with large areas and uneven population distribution, such as the United States, China, and Brazil 53 . Moreover, solely selecting geographic areas with confirmed cases as samples for statistical analysis is prone to sample selection bias 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding sample selection, the use of national-level samples alone fails to account for the regional variations in weather conditions among countries with large areas and uneven population distribution, such as the United States, China, and Brazil 53 . Moreover, solely selecting geographic areas with confirmed cases as samples for statistical analysis is prone to sample selection bias 53 . However, these methods have certain limitations and may lead to estimation bias since the data often fail to meet the underlying assumptions of the methods.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 spread might influence by political, social, geographical, and climatic factors [ 7 ]. Generally, it is believed that weather variables play a significant role in infectious diseases like Spanish influenza, SARS-COV, and MERS-COV [ 8 ]. In a study, Dalziel et al [ 9 ] mentioned that virus spread is linked to factors like temperature, population density, and humidity.…”
Section: Introductionmentioning
confidence: 99%